Community participation in HIV cure research: perspectives from Thailand - Nittaya Phanuphak; Praphan Phanuphak; Nimitr Tien-Udom (Elsevier, 2015)
Thailand aims to end its AIDS epidemic by 2030, and key strategies to effect this include an increase in HIV testing coverage to 90% for key populations (i.e. men who have sex with men, sex workers, people who inject drugs and partners of people living with HIV) and antiretroviral treatment (ART) initiation for all, regardless of CD4 cell count. In order to recruit more key populations into HIV testing, offer immediate ART and retain both HIV-negative people for regular HIV testing and HIV-positive people for continued ART service, effective communication to the community about the clear benefits of early HIV diagnosis and early ART, including the possibility for HIV cure, has become more important than ever. We discuss the need for more innovative ways of communicating.